Enhancing listening achievement through TED Talk-based activities: A mixed-methods study of self-regulated learning - Siti Muawwanah; Yuri Lolita (Metathesis: Journal of English Language, Literature, and Teaching, 2026)
Many Indonesian EFL students lack of exposure to English and have difficulties with listening comprehension; more significantly, they are rarely exposed to naturally occurring, authentic spoken discourse in their learning environments, which can better mirror their needs in real-world communication. The study was a classroom-based study on the application of TED Talks in English Club activities in a senior high school and investigated how it could impact not only students' listening achievement of students, but also their use of self-regulated learning strategies. This was done during the implementation by way of listening tests, questionnaires, and a weekly learning journal written by the students. The listening results of the students were significantly improved with a statistically significant difference (p < 0.05) and a high effect size reported, as the mean score of the students on the pre-test was 64.11 and the post-test was 81.04. Along with the test results, the data from the journal and questionnaire revealed that the majority of students could plan, monitor, and control their learning when they engaged in listening activities.